МЕТОДОЛОГІЯ ПРОЄКТУВАННЯ ІНФОРМАЦІЙНО-АНАЛІТИЧНИХ СИСТЕМ АДМІНІСТРАТИВНОГО УПРАВЛІННЯ - TROFYMCHUK, O.; NESTERENKO, O.; NETESIN, I. (PH “Akademperiodyka”, 2022)
Introduction. In the field of administrative management, the intensity of management activities and the amount of information that needs to be processed for decision-making are constantly growing. In these conditions, the use of new information technologies in the analytical information activities of administrative bodies and the construction of appropriate automated systems is of particular importance.Problem Statement. There is an urgent need for a new approach to solving problems related to the develop ment of analytical information activities and the automation of administrative activities of the authorities. Such an approach should be based on information, consider the modern idea of information as an intellectual product, i.e. knowledge, and as a resource of society, and ensure the complexity of solutions.Purpose. The purpose of this research is to develop a methodology for designing analytical systems based on the integration of concepts, models, methods and information technologies, given the requirements for the comp lexity of solutions.Materials and Methods. The methodology is based on concepts, models, methods, and information technologies, given the requirements for complexity, support for management decisions based on knowledge-oriented tools, their comprehensive information support, support for document processing, information and cybersecurity, as well as the integration of analytical information systems with interoperability.Results. Based on the study, an example of methodology for building a typical information and analytical system of administrative bodies has been proposed. It can be used in the construction of automated systems in various governments, in particular regional government.Conclusions. The theoretical foundation is the regulations for the processing of document flows in the administrative authorities, based on the requirements of the policy of enforcement. The practical significance of the obtained results is the creation of a scientific and methodological framework for building analytical information systems in various areas of administrative management.